عقد االحتراف الرياضي -عقد الالعب أنموذجا- - احلام طالح -عثمان تيطراوي (جامعة المسيلة, 2024)
لقد أصبحت الرياضة اليوم ظاهرة مميزة في حياة اإلنسان، تأخذ مكانة هامة على كل المستويات، وأمام شمولية وأهمية األهداف الموكلة للنشاط الرياضي نشأت ضرورة تأطيره قانونا، وعلى ضوء ذلك ظهر عقد االحتراف الرياضي الذي هو موضوع بحثنا الذي تناولنا دراسته وفق المنهج التحليلي، والمقصود بعقد االحتراف هو العقد المبرم بين الالعب المحترف والنادي الرياضي يلتزم بمقتضاه الالعب أن يضع كامل عطاءه الرياضي في خدمة النادي لقاء أجر يلتزم النادي بتأديته الى الالعب، ويعتبر عقد الالعب المحترف أهم صور عقد االحتراف حيث يتميز بمميزات عامة يتشاركها مع بقية العقود و ينفرد بممي ازت أخرى خاصة به، ويمر بم ارحل النعقاده وفق شروط عامة وأخرى خاصة، وينتج آثا ار قانونية وينشأ حقوقا والت ازمات تقع على عاتق كل طرف. لذلك يوصي هذا البحث بضرورة انشاء تنظيم قانوني خاص بعقد االحتراف الرياضي نظرا لخصوصية النشاط الرياضي. الكلمات المفتاحية: عقد االحتراف الرياضي، الالعب المحترف، النادي الرياضي. Abstract Today, sport has become a distinctive phenomenon in human life, taking an important place at all levels, and in view of the comprehensiveness and importance of the objectives entrusted to sports activity, it arose to frame it legally, and in light of this, the professional sports contract appeared, which is the subject of our research, which we studied according to the analytical method, and the professional contract means the contract concluded between the professional player and the sports club The professional player contract is considered the most important form of the professional contract, as it is characterized by general features that it shares with other contracts and other features that are unique to it, and it passes through stages of its conclusion according to general and special conditions, and produces legal effects and creates rights and obligations that fall on each party. Therefore, this research recommends the necessity of establishing a special legal organization for the professional sports contract due to the specificity of the sports activity. Keywords : Professional sports contract, professional player, sports club.
Keywords: عقد االحتراف الرياضي، الالعب المحترف، النادي الرياضي.